Method for ultrasonic-assisted microwave synthesis of cathode materials

CN122977369APending Publication Date: 2026-10-27GUANGXI UNIV FOR NATITIES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610887863.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-27

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of battery energy storage, and discloses a method for synthesizing a positive electrode material by ultrasonic assistance and microwave, which comprises the following steps: (1) carbonizing multi-walled carbon nanotubes in an ammonia atmosphere, introducing argon after the carbonization is completed, and naturally cooling to obtain nitrogen-doped multi-walled carbon nanotubes; (2) adding a strong oxidant to the nitrogen-doped multi-walled carbon nanotubes, performing ultrasonic dispersion, condensing and refluxing, filtering, then washing with a sodium hydroxide solution until neutral, washing with deionized water, and drying to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes; and (3) mixing the carboxylated nitrogen-doped multi-walled carbon nanotubes with cyclodextrin powder, adding deionized water, then performing ultrasonic dispersion and microwave reaction, filtering, washing and drying after the reaction is completed to obtain the positive electrode material. The application realizes efficient and low-consumption production through the microwave-ultrasonic synergistic effect, and guarantees high performance through uniform dispersion and targeted heating, so that efficient preparation, low-consumption production and high-quality products are finally realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery energy storage technology, and more specifically, to a method for synthesizing cathode materials using ultrasound-assisted microwave synthesis. Background Technology

[0002] Zinc-bromine static batteries eliminate the need for expensive ion exchange membranes and circulating separation liquid storage systems, offering both high safety and low cost advantages, making them a technologically promising approach for large-scale energy storage. This battery uses Zn... 2+ / Zn is the negative electrode, Br2 / Br - As a positive electrode pair, traditional carbon-based positive electrodes suffer from large charging polarization and Br3 - The core problem of its easy diffusion to the negative electrode, causing severe self-discharge, restricts its practical application.

[0003] In the prior art, patent CN119764469A discloses a method for preparing a cyclodextrin-nitrogen-doped multi-walled carbon nanotube cathode material. The method involves calcining the carbon nanotubes in an ammonia atmosphere to introduce nitrogen doping and catalytic sites, followed by carboxylation with a strong oxidant to provide reaction sites. Then, esterification of the cyclodextrin with the carboxylated nitrogen-doped multi-walled carbon nanotubes is achieved through oil bath heating and stirring, fixing the cyclodextrin onto the surface of the carbon nanotubes, thus obtaining a cathode material that combines Br₂ and Br₃. - / Br3 - A cathode material with enriched structure and highly efficient catalytic sites effectively improves the charging polarization and self-discharge problems of zinc-bromine static batteries.

[0004] However, the existing esterification process has significant drawbacks: using traditional oil bath heating and mechanical stirring, the esterification reaction needs to be continuously stirred at 60-80℃ for 18-20 hours, resulting in an extremely long reaction cycle; mechanical stirring has low mass transfer efficiency and insufficient material interface contact, limiting the efficiency of the esterification reaction; long-term oil bath heating has high energy consumption, low production efficiency, and high cost, which does not conform to the concept of green manufacturing and is difficult to meet the needs of large-scale mass production.

[0005] Therefore, developing cathode materials with short reaction times, low energy consumption, and high mass transfer efficiency is of great practical significance. Summary of the Invention

[0006] In view of this, the present invention proposes a method for synthesizing cathode materials using ultrasound-assisted microwave, aiming to solve the problems in the current technology, such as excessively long esterification reaction cycle, extremely low production efficiency, high reaction energy consumption, low mass transfer efficiency, uneven material reaction, poor process adaptability, and difficulty in balancing efficiency and performance.

[0007] This invention proposes a method for synthesizing cathode materials using ultrasound-assisted microwave synthesis, comprising the following steps: (1) Multi-walled carbon nanotubes were calcined in an ammonia atmosphere. After calcination, argon gas was introduced and the tubes were naturally cooled to obtain nitrogen-doped multi-walled carbon nanotubes. (2) A strong oxidant was added to the nitrogen-doped multi-walled carbon nanotubes, and after ultrasonic dispersion, the mixture was refluxed, filtered, washed with sodium hydroxide solution until neutral, washed with deionized water and dried to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes. (3) The carboxylated nitrogen-doped multi-walled carbon nanotubes are mixed with cyclodextrin powder and then deionized water is added. After ultrasonic dispersion and microwave reaction, the mixture is filtered, washed and dried to obtain the cathode material.

[0008] Furthermore, the calcination parameters in step (1) are: temperature 300-450℃ and time 6-10h.

[0009] Furthermore, in step (1), the ammonia gas is introduced for 15-30 minutes before calcination, and the gas flow rate of ammonia gas during calcination is 20-25 mL / min; the argon gas is introduced for 15-30 minutes.

[0010] Furthermore, the ultrasonic dispersion parameters in step (2) are: rotation speed 1000-1200 rpm, time 30-40 min; the condensation reflux parameters are: temperature 40-80℃, time 6-12 h.

[0011] Furthermore, the concentration of the sodium hydroxide solution in step (2) is 0.1-0.5 mol / L; the drying parameters are: temperature 70-85℃ and time 8-10h.

[0012] Furthermore, the strong oxidant mentioned in step (2) is potassium permanganate, concentrated nitric acid, or a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3-4:1.

[0013] Furthermore, the cyclodextrin mentioned in step (3) is one or more of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-α-cyclodextrin, hydroxyethyl-β-cyclodextrin and hydroxypropyl-γ-cyclodextrin; the mass ratio of the carboxylated nitrogen-doped multi-walled carbon nanotubes to the cyclodextrin powder is 1:10.

[0014] Furthermore, the ultrasonic dispersion time in step (3) is 30-60 min; the microwave reaction parameters are: power 300-500 W, temperature 60-80 °C, and time 2-3 h.

[0015] Furthermore, the filtration in step (3) involves washing with ultrapure water 5-7 times; the drying parameters are: temperature 60-80℃ and time 8-12h.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention shortens the esterification reaction time and improves the reaction efficiency of cathode material preparation through the synergistic effect of microwave and ultrasound, and significantly shortens the production cycle of a single batch. It solves the problem of low production efficiency caused by long reaction time in the prior art, and provides a feasible path for the large-scale mass production of zinc-bromine static battery cathode materials.

[0017] In this invention, microwave selective heating can act on reactive polar groups such as carboxyl and hydroxyl groups, reducing the heat loss of traditional oil bath heating; at the same time, ultrasonic cavitation mass transfer replaces mechanical stirring, reducing power consumption, thus reducing the total energy consumption of the reaction stage and generating no additional pollutants, which is in line with the industrial development trend of low carbon and environmental protection and reduces the overall cost of industrial production.

[0018] While innovating the process, the invention maintains the core design of nitrogen-doped catalytic sites in the cathode material and cyclodextrin enrichment structure. Furthermore, the ultrasonic cavitation effect enhances the material interface contact, resulting in a more complete esterification reaction and a more uniform product structure.

[0019] Existing technologies rely on mechanical stirring to mix materials, which can easily lead to the aggregation of carboxylated nitrogen-doped multi-walled carbon nanotubes (NCNTs-COOH) and insufficient contact between cyclodextrin and carboxyl groups, posing a risk of incomplete local reactions. In contrast, this invention uses ultrasonic cavitation to generate microjets and shock waves, breaking up material aggregation and achieving uniform dispersion at the molecular level. At the same time, microwave-directed heating of the reaction sites makes the esterification reaction more thorough, improves the consistency of product structure, and effectively improves the batch performance fluctuation problem that may exist in existing technologies.

[0020] The industrial equipment used in this invention has a simple and controllable operation process and can be adapted to existing production lines without complex modifications. Moreover, the process parameters are reasonable and the stability is high. Compared with the oil bath and mechanical stirring combination used in the prior art, it is easier to achieve automated and continuous production and is suitable for large-scale industrial application scenarios.

[0021] Existing technologies, if they simply shorten the reaction time, will lead to insufficient esterification. If they ensure sufficient reaction, they must bear high energy consumption, creating a contradiction that is difficult to balance. This invention, through the synergistic mechanism of rapid heating and efficient mass transfer, significantly improves efficiency and reduces energy consumption while optimizing material properties. It completely solves the core problem of the incompatibility between efficiency, energy consumption, and performance in existing technologies, and takes into account both technological advancement and practical application value. Detailed Implementation

[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.

[0023] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0024] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0025] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0026] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0027] This invention proposes a method for synthesizing cathode materials using ultrasound-assisted microwave synthesis, comprising the following steps: (1) Multi-walled carbon nanotubes were calcined in an ammonia atmosphere. After calcination, argon gas was introduced and the tubes were naturally cooled to obtain nitrogen-doped multi-walled carbon nanotubes. (2) A strong oxidant was added to the nitrogen-doped multi-walled carbon nanotubes, and after ultrasonic dispersion, the mixture was refluxed, filtered, washed with sodium hydroxide solution until neutral, washed with deionized water and dried to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes. (3) The carboxylated nitrogen-doped multi-walled carbon nanotubes are mixed with cyclodextrin powder and then deionized water is added. After ultrasonic dispersion and microwave reaction, the mixture is filtered, washed and dried to obtain the cathode material.

[0028] In this invention, the calcination parameters in step (1) are preferably: temperature 300-450℃ and time 6-10h, and more preferably temperature 350-450℃ and time 6-9h.

[0029] In this invention, the ammonia gas in step (1) is preferably introduced for 15-30 min before calcination, and the gas flow rate of ammonia gas during calcination is 20-25 mL / min, more preferably introduced for 18-30 min before calcination, and the gas flow rate of ammonia gas during calcination is 22-25 mL / min; the argon gas is preferably introduced for 15-30 min, more preferably 18-30 min.

[0030] In this invention, the ultrasonic dispersion parameters in step (2) are preferably: rotation speed 1000-1200 rpm and time 30-40 min, and more preferably 1100-1200 rpm and time 30-38 min; the condensation reflux parameters are preferably: temperature 40-80℃ and time 6-12 h, and more preferably 42-80℃ and time 6-11 h.

[0031] In this invention, the concentration of the sodium hydroxide solution in step (2) is preferably 0.1-0.5 mol / L, more preferably 0.2-0.5 mol / L; the drying parameters are preferably: temperature 70-85℃ and time 8-10h, more preferably temperature 73-85℃ and time 8-9h.

[0032] In this invention, the strong oxidant in step (2) is preferably potassium permanganate, concentrated nitric acid, or a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3-4:1.

[0033] In this invention, the cyclodextrin in step (3) is one or more of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-α-cyclodextrin, hydroxyethyl-β-cyclodextrin and hydroxypropyl-γ-cyclodextrin; the mass ratio of the carboxylated nitrogen-doped multi-walled carbon nanotubes to the cyclodextrin powder is 1:10.

[0034] In this invention, the ultrasonic dispersion time in step (3) is preferably 30-60 min, and more preferably 40-60 min; the microwave reaction parameters are preferably: power 300-500 W, temperature 60-80 °C, time 2-3 h, and more preferably power 350-500 W, temperature 65-80 °C, time 2.5-3 h.

[0035] In this invention, microwave heating combined with ultrasonic dispersion enhances mass transfer, shortening the esterification reaction time and improving reaction efficiency. This completely overcomes the bottleneck of long reaction times caused by traditional heating methods, making it suitable for large-scale mass production. Furthermore, the high-frequency electromagnetic field of microwaves can activate the polarity of carboxyl and hydroxyl groups, reducing the activation energy of the esterification reaction and accelerating the chemical bonding rate. Compared to traditional oil bath heating, which only provides reaction motive force by increasing temperature, microwave heating not only raises the temperature but also activates the reaction molecules, making the esterification reaction more thorough. The power and temperature of microwave heating can be precisely controlled by instruments, with rapid heating and cooling rates and easy control of the reaction endpoint, avoiding the problems of temperature lag and large fluctuations in traditional oil bath heating. At the same time, the microwave reactor can achieve a closed reaction, reducing solvent evaporation and environmental interference, making operation safer and more environmentally friendly. It does not require a complex temperature calibration process and is easy to coordinate with ultrasonic equipment to achieve automated and continuous production, making it suitable for large-scale industrial preparation scenarios.

[0036] Furthermore, compared to traditional oil bath heating, which relies on heat conduction and is prone to temperature gradients with high container wall temperatures and low center temperatures, leading to incomplete local reactions and uneven product structures, microwave heating in this invention heats the material simultaneously, resulting in a uniform temperature distribution within the system. Combined with the dispersing effect of ultrasonic cavitation, this ensures uniform contact and esterification reaction between NCNTs-COOH and cyclodextrin at the molecular level. This results in more consistent cyclodextrin loading and nitrogen-doped catalytic site exposure in the product, leading to smaller fluctuations in charge-discharge voltage difference and stable energy retention during static discharge of the prepared cathode material. This solves the batch performance fluctuation problem that may exist in existing technologies.

[0037] In this invention, the carboxylated nitrogen-doped multi-walled carbon nanotubes, as carbon-based materials, are prone to agglomeration due to van der Waals forces, forming micron-sized aggregates that hinder the sufficient contact between cyclodextrin and its surface carboxyl groups. The cavitation effect of ultrasound can strongly disperse these NCNTs-COOH aggregates, while simultaneously dispersing the cyclodextrin powder uniformly in the aqueous solution, resulting in a molecular-level homogeneous mixture of the two reactants. Compared to the macroscopic forced mixing in existing mechanical stirring techniques, which still carries the risk of localized agglomeration, the ultrasonic dispersion method in this invention increases the material contact area several times, facilitating rapid subsequent esterification reactions. The invention lays a solid foundation; the uniform dispersion effect of ultrasound avoids the problem of excessively high / low local reactant concentrations caused by traditional mechanical stirring, ensuring that the carboxyl groups on the surface of each NCNTs-COOH react uniformly with the cyclodextrin hydroxyl groups, resulting in a more uniform cyclodextrin loading and loading site distribution in the final product; moreover, in this invention, ultrasound directly replaces the mechanical stirring step of the prior art, not only saving the power consumption of the stirring equipment, but also avoiding the risk of contamination of the reaction system by the stirring paddle; at the same time, ultrasonic dispersion can be carried out simultaneously with microwave heating, without the need for additional step operations, simplifying the process flow.

[0038] This invention generates microjets and shock waves through ultrasonic cavitation effect, breaking up material agglomeration and strengthening molecular-level interfacial contact. At the same time, microwave directional heating of reaction sites achieves microscopic uniform contact and directional acceleration of reaction, thus solving the problems of inefficient mass transfer and uneven reaction of traditional mechanical stirring from a mechanistic perspective.

[0039] In this invention, the filtration in step (3) is preferably washing with ultrapure water 5-7 times, more preferably 5-6 times; the drying parameters are preferably: temperature 60-80℃, time 8-12h, more preferably temperature 65-80℃, time 8-10h.

[0040] In this invention, the method for synthesizing cathode materials using ultrasound-assisted microwave heating selects a synergistic effect of microwave heating and ultrasonic dispersion. The microwave rapidly and directionally raises the temperature, eliminating the need for heat conduction and quickly raising the reaction sites (carboxyl and hydroxyl groups) to the target temperature, avoiding temperature lag. The ultrasonic cavitation effect breaks up material agglomeration, achieving molecular-level dispersion and increasing the contact area of ​​reactants several times, thus enhancing interfacial mass transfer. The simultaneous operation of these two technologies creates a synergistic effect of rapid heating and efficient mass transfer, shortening the esterification reaction time, improving efficiency, and significantly reducing the production cycle per batch. This directly meets the needs of large-scale mass production, and while significantly shortening the reaction time and reducing energy consumption, it maintains the core performance of the cathode material. In contrast, traditional oil bath heating relies on heat conduction for heating, which is slow and has a temperature gradient. Combined with macroscopic mixing by mechanical stirring, the mass transfer efficiency is low.

[0041] In this invention, unless otherwise specified, all raw materials required for preparation are commercially available products well known to those skilled in the art.

[0042] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0043] Example 1 (1) Multi-walled carbon nanotubes were calcined in an ammonia atmosphere for 9 hours at a calcination temperature of 350℃. Ammonia was introduced for 18 minutes before calcination and the gas flow rate of ammonia was 22 mL / min during calcination. After calcination, argon was introduced for 18 minutes to remove residual ammonia and the tubes were naturally cooled to obtain nitrogen-doped multi-walled carbon nanotubes. (2) Potassium permanganate, a strong oxidant, was added to the nitrogen-doped multi-walled carbon nanotubes and ultrasonically dispersed at 1100 rpm for 38 min. Then, the mixture was refluxed at 42 °C for 11 h, filtered, washed with 0.2 mol / L sodium hydroxide solution until neutral, washed with deionized water, and dried at 73 °C for 9 h to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes. (3) The carboxylated nitrogen-doped multi-walled carbon nanotubes and α-cyclodextrin powder were mixed at a mass ratio of 1:10 and then deionized water was added. After ultrasonic dispersion for 40 min and microwave reaction at 350 W and 65 °C for 3 h, the reaction was filtered, washed 5 times with ultrapure water and dried at 65 °C for 10 h to obtain the cathode material.

[0044] Example 2 (1) Multi-walled carbon nanotubes were calcined in an ammonia atmosphere for 8 hours at a calcination temperature of 380℃. Ammonia was introduced for 20 minutes before calcination and the gas flow rate of ammonia during calcination was 23 mL / min. After calcination, argon was introduced for 20 minutes to remove residual ammonia and the tubes were naturally cooled to obtain nitrogen-doped multi-walled carbon nanotubes. (2) Add concentrated nitric acid, a strong oxidant, to the nitrogen-doped multi-walled carbon nanotubes and ultrasonically disperse them at 1150 rpm for 32 min. Then, reflux them at 50 °C for 10 h, filter them, wash them with 0.3 mol / L sodium hydroxide solution until neutral, wash them with deionized water, and dry them at 75 °C for 8.5 h to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes. (3) The carboxylated nitrogen-doped multi-walled carbon nanotubes and β-cyclodextrin powder were mixed at a mass ratio of 1:10 and then deionized water was added. After ultrasonic dispersion for 45 min and microwave reaction at 400 W and 68 °C for 2.5 h, the reaction was filtered, washed 5 times with ultrapure water and dried at 70 °C for 8.5 h to obtain the cathode material.

[0045] Example 3 (1) Multi-walled carbon nanotubes were calcined in an ammonia atmosphere for 7 hours at a calcination temperature of 400℃. Ammonia was introduced for 25 minutes before calcination and the gas flow rate of ammonia was 24 mL / min during calcination. After calcination, argon was introduced for 25 minutes to remove residual ammonia and the tubes were naturally cooled to obtain nitrogen-doped multi-walled carbon nanotubes. (2) Add a strong oxidant mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 4:1 to the nitrogen-doped multi-walled carbon nanotubes, ultrasonically disperse at 1200 rpm for 30 min, then reflux at 60 °C for 9 h, filter, then wash with 0.4 mol / L sodium hydroxide solution until neutral, then wash with deionized water and dry at 78 °C for 8.5 h to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes; (3) The carboxylated nitrogen-doped multi-walled carbon nanotubes and γ-cyclodextrin powder were mixed at a mass ratio of 1:10 and then deionized water was added. After ultrasonic dispersion for 50 min and microwave reaction at 450 W and 75 °C for 2.5 h, the reaction was filtered, washed with ultrapure water 6 times and dried at 75 °C for 9 h to obtain the cathode material.

[0046] Example 4 (1) Multi-walled carbon nanotubes were calcined in an ammonia atmosphere for 6 hours at a calcination temperature of 450℃. Ammonia was introduced for 30 minutes before calcination and the gas flow rate of ammonia was 25 mL / min during calcination. After calcination, argon was introduced for 30 minutes to remove residual ammonia and the tubes were naturally cooled to obtain nitrogen-doped multi-walled carbon nanotubes. (2) Add a strong oxidant mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 to the nitrogen-doped multi-walled carbon nanotubes, ultrasonically disperse at 1200 rpm for 30 min, then reflux at 80 °C for 6 h, filter, then wash with 0.5 mol / L sodium hydroxide solution until neutral, then wash with deionized water and dry at 85 °C for 8 h to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes; (3) The carboxylated nitrogen-doped multi-walled carbon nanotubes and hydroxypropyl-α-cyclodextrin powder were mixed at a mass ratio of 1:10 and then deionized water was added. After ultrasonic dispersion for 60 min and microwave reaction at 500 W and 80 °C for 2.5 h, the reaction was filtered, washed with ultrapure water 6 times and dried at 80 °C for 8 h to obtain the cathode material.

[0047] Comparative Example 1 (1) Multi-walled carbon nanotubes were calcined in an ammonia atmosphere for 8 hours at a calcination temperature of 380℃. Ammonia was introduced for 20 minutes before calcination and the gas flow rate of ammonia was 23 mL / min during calcination. After calcination, argon was introduced for 20 minutes to remove residual ammonia and the tubes were naturally cooled to obtain nitrogen-doped multi-walled carbon nanotubes. (2) Add concentrated nitric acid, a strong oxidant, to the nitrogen-doped multi-walled carbon nanotubes and ultrasonically disperse them at 1150 rpm for 32 min. Then, reflux them at 50 °C for 10 h, filter them, wash them with 0.3 mol / L sodium hydroxide solution until neutral, wash them with deionized water, and dry them at 75 °C for 8.5 h to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes. (3) The carboxylated nitrogen-doped multi-walled carbon nanotubes and β-cyclodextrin powder were mixed at a mass ratio of 1:10 and then deionized water was added. The mixture was ultrasonically dispersed for 45 min and then transferred to an oil bath. The mixture was mechanically stirred at 68°C for 18 h. After the reaction was completed, the mixture was filtered, washed 5 times with ultrapure water, and dried at 70°C for 8.5 h to obtain the cathode material.

[0048] Comparative Example 2 (1) Multi-walled carbon nanotubes were calcined in an ammonia atmosphere for 7 hours at a calcination temperature of 400℃. Ammonia was introduced for 25 minutes before calcination and the gas flow rate of ammonia was 24 mL / min during calcination. After calcination, argon was introduced for 25 minutes to remove residual ammonia and the tubes were naturally cooled to obtain nitrogen-doped multi-walled carbon nanotubes. (2) Add a strong oxidant mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 4:1 to the nitrogen-doped multi-walled carbon nanotubes, ultrasonically disperse at 1200 rpm for 30 min, then reflux at 60 °C for 9 h, filter, then wash with 0.4 mol / L sodium hydroxide solution until neutral, then wash with deionized water and dry at 78 °C for 8.5 h to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes; (3) The carboxylated nitrogen-doped multi-walled carbon nanotubes and γ-cyclodextrin powder were mixed at a mass ratio of 1:10 and then deionized water was added. The mixture was ultrasonically dispersed for 50 min and then transferred to an oil bath. The mixture was mechanically stirred at 75°C for 20 h. After the reaction was completed, the mixture was filtered, washed with ultrapure water 6 times, and dried at 75°C for 9 h to obtain the cathode material.

[0049] Performance testing: (1) Electrochemical tests were conducted on the zinc-bromine static batteries of each embodiment and each comparative example to investigate their charging polarization and self-discharge performance. The experimental conditions were as follows: The test temperature was 25℃; the charging and discharging current densities were the same, using two current densities: 10 and 40 mA / cm². 2 The charging cutoff voltage is 1.8V, and the discharging cutoff voltage is 0.6V. The severity of battery charging polarization is assessed by the voltage difference between the charging and discharging plateaus. For self-discharge performance, the battery's energy retention rate after being charged to the cutoff voltage and left to stand for 4 days is used as a comparison.

[0050] (2) The battery performance test results are shown in Table 1 below: Table 1. Battery performance test results for both the examples and comparative examples. (3) The results show that the charge-discharge voltage difference in Examples 1-4 is 265-295mV / 10mA / cm. 2 318-360mV / 40mA / cm 2 All were significantly lower than the 385-392 mV / 10 mA / cm of Comparative Examples 1-2. 2 482-495mV / 40mA / cm 2 This indicates that the materials prepared by the microwave-ultrasound synergistic process have higher catalytic activity and weaker charging polarization; the static discharge energy retention rate of Examples 1-4 is 75%-83% / 10mA / cm. 2 72%-81% / 40mA / cm 2 It is much higher than the 56%-58% / 10mA / cm of comparative examples 1-2. 2 53%-55% / 40mA / cm 2 This indicates that ultrasonic dispersion allows for more complete fixation of cyclodextrin, Br3 -The enrichment and diffusion inhibition effects are superior; and the esterification reaction time in Examples 1-4 is only 12.5%-16.7% of that in the prior art, with energy consumption in the reaction stage reduced by 68%-72%, resulting in better performance; furthermore, different cyclodextrin types in Examples 1-4 are adapted to this synergistic process, resulting in stable product performance, small batch-to-batch fluctuations, and strong process adaptability, providing reliable support for large-scale mass production. Therefore, the preparation method of the cathode material described in this invention has a synergistic effect of high efficiency, low energy consumption, and high performance.

[0051] In summary, this invention first introduces pyridine nitrogen onto multi-walled carbon nanotubes, then performs surface activation and incorporation of carboxyl groups, and finally employs a synergistic process of microwave heating and ultrasonic dispersion to promote a rapid and efficient esterification reaction between the carboxyl groups and the hydroxyl groups in the cyclodextrin molecule, thereby immobilizing the cyclodextrin on nitrogen-doped multi-walled carbon nanotubes, thus producing a product with both Br / Br3... - A cathode material with enriched structure and highly efficient catalytic sites is used to prepare the cathode for a zinc-bromine static battery. During charging, cyclodextrin enriches Br. - , Pyridine nitrogen catalysis Br - Oxidation synergistically enhances mass transfer and reactivity, significantly reducing charging polarization; during storage, cyclodextrin efficiently retains Br3. - This process inhibits the diffusion of the material to the negative electrode, significantly improving self-discharge performance. Furthermore, compared to traditional oil bath heating and mechanical stirring processes, this synergistic process shortens the esterification reaction time from 18-20 hours to 2-3 hours, reducing energy consumption by 70%, achieving green and efficient preparation of the positive electrode material, and completely solving the problems of long processing times, high energy consumption, and product performance fluctuations associated with traditional processes.

[0052] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention. The scope of protection of the present invention is determined by the appended claims.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for synthesizing cathode materials using ultrasound-assisted microwave synthesis, characterized in that, Includes the following steps: (1) Multi-walled carbon nanotubes were calcined in an ammonia atmosphere. After calcination, argon gas was introduced and the tubes were naturally cooled to obtain nitrogen-doped multi-walled carbon nanotubes. (2) A strong oxidant was added to the nitrogen-doped multi-walled carbon nanotubes, and after ultrasonic dispersion, the mixture was refluxed, filtered, washed with sodium hydroxide solution until neutral, washed with deionized water and dried to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes. (3) The carboxylated nitrogen-doped multi-walled carbon nanotubes are mixed with cyclodextrin powder and then deionized water is added. After ultrasonic dispersion and microwave reaction, the mixture is filtered, washed and dried to obtain the cathode material.

2. The method for synthesizing a cathode material using ultrasound-assisted microwave according to claim 1, characterized in that, The calcination parameters in step (1) are: temperature 300-450℃ and time 6-10h.

3. The method for ultrasonic-assisted microwave synthesis of cathode materials according to claim 1, characterized in that, The ammonia gas mentioned in step (1) is introduced for 15-30 minutes before calcination, and the gas flow rate of ammonia gas during calcination is 20-25 mL / min; the argon gas is introduced for 15-30 minutes.

4. The method for synthesizing a cathode material using ultrasound-assisted microwave according to claim 1, characterized in that, The ultrasonic dispersion parameters in step (2) are: rotation speed 1000-1200 rpm, time 30-40 min; the condensation reflux parameters are: temperature 40-80℃, time 6-12 h.

5. The method for synthesizing a cathode material using ultrasound-assisted microwave according to claim 1, characterized in that, The concentration of the sodium hydroxide solution in step (2) is 0.1-0.5 mol / L; the drying parameters are: temperature 70-85℃ and time 8-10h.

6. The method for synthesizing a cathode material using ultrasound-assisted microwave according to claim 1, characterized in that, The strong oxidant mentioned in step (2) is potassium permanganate, concentrated nitric acid, or a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3-4:

1.

7. The method for synthesizing a cathode material using ultrasound-assisted microwave according to claim 1, characterized in that, The cyclodextrin mentioned in step (3) is one or more of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-α-cyclodextrin, hydroxyethyl-β-cyclodextrin and hydroxypropyl-γ-cyclodextrin; the mass ratio of the carboxylated nitrogen-doped multi-walled carbon nanotubes to the cyclodextrin powder is 1:

10.

8. The method for ultrasonic-assisted microwave synthesis of cathode materials according to claim 1, characterized in that, The ultrasonic dispersion time in step (3) is 30-60 min; the microwave reaction parameters are: power 300-500 W, temperature 60-80 °C, and time 2-3 h.

9. The method for synthesizing a cathode material using ultrasound-assisted microwave according to claim 1, characterized in that, The filtration in step (3) involves washing with ultrapure water 5-7 times; the drying parameters are: temperature 60-80℃ and time 8-12h.

Citation Information

Patent Citations

  • Preparation method and application of zinc-bromine static battery positive electrode material

    CN119764469A